Aortic Dissection Presented As STEMI: How to diagnosis? - Wisnu Agung Wiyangga; Mohamad Satrio Goma; Yandi Ariffudin (ARKAVI [Arsip Kardiovaskular Indonesia), 2020)
2% per hour reported in the first several hour ofonset. A 36-Year-Old man admitted to emergency department with abruptonset heavy pain in his epigastric. Trans-thoracic echocardiography (TTE)was suggestive AD stanford A debakey type I. Patient had been referred toundergoing ascending aortic hemiarch replacement. It is important toperform routine bedside TTE on high suspicious of aortic dissection and RVinfarction patient. Maintenance of lowblood pressure is critical in this patientand urgent transfer to high facilities is needed. Keywords: Aortic Dissection, Hemiarch Replacement Right VentricularInfarction, STEMI, TTE